Drug-Induced Atrial Fibrillation Complicates the Results of Flap Surgery in a Rat Model. Issue 2 (February 2016) - Sakisaka, Masanobu; Kurita, Masakazu; Okazaki, Mutsumi; Kagaya, Yu; Takushima, Akihiko; Harii, Kiyonori
Abstract : Abstract: The relationship between atrial fibrillation (AF) and flap survival has not been fully characterized. Therefore, the goal of this study was to investigate the effect of AF on survival areas of pedicled flap and survival rates of free flap in an experimental rat AF model. An aconitine-induced rat AF model was established without intubation anesthesia. Survival areas of the pedicled rectangular epigastric flap were compared between AF rats (n = 7) and control rats (n = 7), and survival rates of the free epigastric flap were compared between AF rats (n = 10) and control rats (n = 10). Animals that died during the study or in which AF was not induced were excluded from study. A total of 64 rats were assessed in this study. Atrial fibrillation was induced with a success rate of 77.8% (21/27) throughout the study. Pedicled flap survival area was significantly higher in controls (75.1 ± 9.0%; n = 7) than that in AF animals (55.7 ± 13.0%; n = 7) ( P < 0.01, nonpaired Student t test). Free flap survival rates were 80% in controls and 40% in AF animals ( P = 0.07, χ 2 test). This is the first study to develop an aconitine-induced model of AF in rats. Atrial fibrillation has a detrimental effect on survival areas of the pedicled flap and survival rates of the free flap.